Terapia ocupacional social: diálogos com a Política Nacional de Assistência Social - Vianna, Eduardo Ewerton Sousa (Universidade Federal de São Carlos, 2013)
The 1988 Brazilian Constitution introduces social welfare as a social security policy and a citizen s right. This way the promulgation of the Organic Law of Social Welfare in 1993 and the creation of a decentralized public system led to the approval of the Social Welfare National Policy (SWNP), whose management is undertaken by the Unified Social Welfare System (USWS). The National Counsil of Welfare, supported by the Ministry of Social Development and Hunger Alleviation (MSD), proposed the debate process for the definition of Social Welfare workers (DPDSWW) and also to help on the definition of the teams that would become responsible for organizing and providing social assistance services. Occupational therapists and other professional groups were included in this process; in the outcome occupation therapy was ratified as an integral part of the USWS. This study aims to contribute to the debate on occupational therapy in USWS by describing mobilizations and arguments for the recognition of its contribution and importance in this context, during the participation of the professional group in the DPDSWW. This is a study which took form with the data collected in the documentary research on the regulatory frameworks of SWNP and USWS, and also with correspondences taken from the online discussion forum of National Workgroup on Occupational Social Therapy (GNTOSOCIAL, in Portuguese) which is organized and coordinated by the Brazilian Association of Occupational Therapists (ABRATO, in Portuguese). Interviews (with three of the protagonists) and questionnaires (performed with nine occupational therapists from GNTOSOCIAL) complemented this data. We were able to identify which occupational therapists and institutions have participated in DPDSWW and how they have worked. We verified that ABRATO organized associations, the METUIA Project, occupational therapists and teachers around the GNTOSOCIAL discussion forum. A national movement was constructed from this list for the participation of the professional group in DPDSWW. This group faced constraints on being present in all regions and participating in debates, seeking consensus and earning new subscriptions to their cause. GNTOSOCIAL s participation was crucial for the outcome of the DPDSWW, as acting foundations for occupational therapists in social warfare were brought to debate. We found that new challenges are being faced by occupational therapists after DPDSWW. However, the modification of curricular guidelines seems urgent, as it should emphasize subjects regarding social occupational therapy and ensure students gain experience from the social welfare network, with qualified tutors in the social field. Research and postgraduate training are important for social occupational therapy when it comes to individuals skill development, their own knowledge and services, which are offered by several social policies.
Occupational Social Therapy: Dialogues with the Social Welfare National Policy
Keywords: Terapia ocupacional; Terapia ocupacional social; Política Nacional de Assistência Social; Sistema Único de Assistência Social (Brasil); Vulnerabilidade social; Social Occupational Therapy; Social Welfare National Policy; Unified Social Welfare System; Occupational Therapy; Social Vulnerability; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL